Circadian Rhythm in Kidney Tissue Oxygenation in the Rat - Emans, Tonja W.; Janssen, Ben J.; Joles, Jaap A.; Krediet, C. T. Paul (Frontiers in Physiology, 2017)
Blood pressure, renal hemodynamics, electrolyte and water excretion all display diurnal oscillation. Disturbance of these patterns is associated with hypertension and chronic kidney disease. Kidney oxygenation is dependent on oxygen delivery and consumption that in turn are determined by renal hemodynamics and metabolism. We hypothesized that kidney oxygenation also demonstrates 24-h periodicity. Telemetric oxygen-sensitive carbon paste electrodes were implanted in Sprague-Dawley rats (250-300g), either in renal medulla (n=9) or cortex (n=7). Arterial pressure (MAP) and heart rate (HR) were monitored by telemetry in a separate group (n=8). Data from 5 consecutive days were analyzed for rhythmicity by cosinor analysis. Diurnal electrolyte excretion was assessed by metabolic cages. During lights-off, oxygen levels increased to 105.3±2.1% in cortex and 105.2±3.8% in medulla. MAP was 97.3±1.5 mmHg and HR was 394.0±7.9 bpm during lights-off phase and 93.5±1.3 mmHg and 327.8±8.9 bpm during lights-on. During lights-on, oxygen levels decreased to 94.6±1.4% in cortex and 94.2±8.5% in medulla. There was significant 24-h periodicity in cortex and medulla oxygenation. Potassium excretion (1737±779 vs. 895±132 μmol/12h, P=0.005) and the distal Na+/K+ exchange (0.72±0.02 vs. 0.59±0.02 P<0.001) were highest in the lights-off phase, this phase difference was not found for sodium excretion (P=0.4). It seems that oxygen levels in the kidneys follow the pattern of oxygen delivery, which is known to be determined by renal blood flow and peaks in the active phase (lights-off).